2004
DOI: 10.1175/1520-0426(2004)021<0995:rbosug>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Radar Beam Occultation Studies Using GIS and DEM Technology: An Example Study of Guam

Abstract: Geographic information systems (GISs) combined with digital elevation models (DEMs) provide opportunities to evaluate weather radar beam blockage and other ground clutter phenomena. The authors explore this potential using topographic information and a simple beam propagation model for the complex terrain of Guam. To evaluate the effect of different DEM resolutions, they compare the simulated patterns of complete and partial beam blockage with probability of detection maps derived from a large database of leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 19 publications
1
37
0
Order By: Relevance
“…Vivekanandan et al (1999) showed that the actual bias in measured reflectivity caused by beam blockage depends on the amount of beam blockage and the reflectivity difference between the precipitation and the ground clutter echo. Therefore, although shielding of the beam over complex terrain is challenging, it is important in producing accurate rainfall estimates (Dinku et al, 2002;Kucera et al, 2004;Germann et al, 2006;Lang et al, 2009).…”
Section: The Challenge Of Radar-based Quantitative Precipitation Estimentioning
confidence: 99%
See 1 more Smart Citation
“…Vivekanandan et al (1999) showed that the actual bias in measured reflectivity caused by beam blockage depends on the amount of beam blockage and the reflectivity difference between the precipitation and the ground clutter echo. Therefore, although shielding of the beam over complex terrain is challenging, it is important in producing accurate rainfall estimates (Dinku et al, 2002;Kucera et al, 2004;Germann et al, 2006;Lang et al, 2009).…”
Section: The Challenge Of Radar-based Quantitative Precipitation Estimentioning
confidence: 99%
“…However, radar estimates of rainfall using ZH in areas of beam blockage are clearly biased compared with ground-truthed data (Zrnic and Ryzhkov, 1996;Vivekanandan et al, 1999;Kucera et al, 2004;Krajewski et al, 2006;Friedrich et al, 2007;Lang et al, 2009;P.C. et al, 2013).…”
Section: The Challenge Of Radar-based Quantitative Precipitation Estimentioning
confidence: 99%
“…If the terrain variation within the area covered by one topographic data point close to the radar is too large, the blockage pattern behind that point may be incorrect. This is a potential problem because of the resolution of the DEM data (Kucera et al, 2004). As relatively small obstacles close to the radar, such as masts, are not resolved by the DEM, corresponding blockages cannot be simulated by the BPM.…”
Section: The Beam-propagation Modelmentioning
confidence: 99%
“…However, PBB-correction schemes based on KDP cannot be applied when radar observations are in snow or ice (Zhang et al, 2013); moreover, many operational weather radar are still in single polarization. As demonstrated in several studies (Kucera et al, 2004;Fornasiero et al, 2006;Krajewski et al, 2006), accurate radar visibility maps can be obtained by applying beam standard atmospheric propagation models (Doviak and Zrnić, 1984) coupled with highresolution digital elevation models (DEMs). Furthermore, Krajewski et al (2006) also demonstrated that PBBs can be successfully estimated by modeling radar visibility using accurate DEM data and a geographic information system (GIS).…”
Section: Introductionmentioning
confidence: 99%